Diversity of Epigeal Ants (Hymenoptera: Formicidae) in Urban Areas of Alto Tiete - de Souza, D. R.; dos Santos, S. G.; Munhae, C. de B. [UNESP]; Morini, M. S. de C. (California State University, 2012)
The objective of this study was to conduct an inventory of the ant fauna, evaluating indicators of diversity, litter community composition and similarity among seven areas located around the city of Mogi das Cruzes (SP). In each area 20 pitfalls were distributed, which remained in the field for seven days. Four samplings were performed, two in the rainy season and two during dry season. In total there were 92 recorded species, 36 genera, 19 tribes and seven subfamilies. The most frequent species belong to the genera Pheidole and Camponotus, both common in the Neotropics. Differences were observed in species composition with the formation of two groups, one under the influence of the Atlantic Forest and other in the urban region. Only one exotic species, Paratrechina longicornis, was recorded. The results indicate the importance of the forest surrounding the city to maintain the biological diversity of ant communities.
Keywords: anthropization; communities; Atlantic Forest; exotic ants; Serra do Itapeti